1981
DOI: 10.1111/j.1095-8649.1981.tb03794.x
|View full text |Cite
|
Sign up to set email alerts
|

Light and electron microscopic studies on the absorptive cells of the intestine, caeca and rectum of the adult rainbow trout, Salmo gairdneri, Rich

Abstract: The absorptive cells lining the mucosa of the intestine, caeca and rectum of farm-reared adult rainbow trout (Salmo guirdneri Rich.) were studied by light and electron microscopy.Most of the intestinal absorptive cells showed morphological characteristics of lipid absorption. The cytoplasm of a few cells was closely packed with mitochondria. The caecal absorptive cells resembled those ofthe intestine but contained more apical dense bodies and more complex lamellar structures which, in conjunction with the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1
7

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 28 publications
(42 reference statements)
5
50
1
7
Order By: Relevance
“…They observed that molecular markers linked to nutrient digestion and absorption were high in the anterior (AI) and middle intestine (MI) while the posterior intestine (PI) predominantly expressed genes linked to immune defence mechanisms. These observations are in line with other scientists who showed that the AI and MI are mainly responsible for nutrient digestion and absorption [104,105] while the PI is responsible for induction of innate immune responses linked to activation of adaptive immunity in teleosts ish [106][107][108][109].…”
Section: Nutrigenomics In Aquaculturesupporting
confidence: 79%
“…They observed that molecular markers linked to nutrient digestion and absorption were high in the anterior (AI) and middle intestine (MI) while the posterior intestine (PI) predominantly expressed genes linked to immune defence mechanisms. These observations are in line with other scientists who showed that the AI and MI are mainly responsible for nutrient digestion and absorption [104,105] while the PI is responsible for induction of innate immune responses linked to activation of adaptive immunity in teleosts ish [106][107][108][109].…”
Section: Nutrigenomics In Aquaculturesupporting
confidence: 79%
“…Proximal portions of fishes' intestines are credited with higher nutrient digestibility and absorption, and overall digestive capacity; the distal portions of fishes' intestines are important for absorption of intact proteins and peptides molecules (Bakke-McKellep et al, 2000;Ezeasor and Stokoe, 1981;Krogdahl et al, 2003;Ledger et al, 2002;Ostaszewska et al, 2005;van den Ingh et al, 1991). This ability of distal intestine may be related to its attributed immunological function (Georgopoulou and Vernier, 1986;Jenkins et al, 1994;Rombout et al, 1985;Rombout and van den Berg, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…The proximal portions of the intestines of fish are related to higher capacity and effective contribution to digestion and nutrient absorption, while the distal region is involved in the absorption of intact proteins and peptides (Krogdahl et al, 2003) -an ability that is related to its immunological role (Buddington et al). In pirarucu, the latter function is most likely performed in the S3 region, where absorption vacuoles were often observed in the apical cytoplasm of enterocytes, which can be indicative of protein absorption by pinocytosis (Ezeasor & Stokoe, 1981;Carrassón et al).…”
Section: Discussionmentioning
confidence: 99%